ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI SEKTOR PERUSAHAAN NON-KEUANGAN - Shofyan Haris, - (2019)
This research was conducted to test the influence of the profitability,liquidity, leverage and firm Size of Bond Rating. Doing research on the NonFinancial Sector company's which listed on the Indonesia Stock Exchange as a sample. The technique of determination of the sample using purposive sampling method. The selection of the sample of 94 company Non-Financial Sector were listed on the Indonesia Stock Exchange in 2014-2017 produce company 21 is acceptable. Data analysis is done using the Microsoft Excel 2013 and hypothesis testing in this study using a Panel Data Regression Analysis with the program Eviews 9 and the level of significance of 5%. The results of the test were obtained (1) the Profitability is represented by ROA effect significantly positive to the Bond Rating, (2) Liquidity is represented by CR effect significantly positive to the Bond Rating, (3) Leverage is represented by DER no effect to the Bond Rating, (4) Firm Size is represented by Size no effect to the Bond Rating.